2024
DOI: 10.1021/acs.energyfuels.3c04545
|View full text |Cite
|
Sign up to set email alerts
|

A Self-Supporting Electrode Material (NiS/NF) as a Stable and Efficient Electrocatalyst for Oxygen Evolution: In Situ Surface Activation of Nickel Sulfide to Nickel Oxide/(Oxy)hydroxide

Murugan Vijayarangan,
Arunagiri Gayathri,
Venkatachalam Ashok
et al.

Abstract: Binder-free nickel sulfide material grown on NF (NiS/NF) by a basic thermal sulfur growth mechanic was employed as both the electrode material and electrode substrate for water oxidation in 1.0 M KOH. In NiS/NF, sulfur was found to be an activator to transform nickel sulfide to nickel oxide/(oxy)­hydroxide. A transmission electron microscopy image of NiS/NF inferred that the oxide/(oxy)­hydroxyl layer was found to be amorphous in nature. The energized NiS/NF electrocatalyst showed superior activity in oxygen e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 45 publications
(72 reference statements)
0
5
0
Order By: Relevance
“…03-1051) of the NF substrate of Co@NC-NPs/NF. Confirmatively, the as-synthesized Co@NC-NPs catalyst retained its amorphous nature after HER . The nanochain agglomeration and maintaining the amorphous nature of the electrocatalyst reveal that the nitrogen-doped carbon matrix encapsulated on the surface of cobalt (Co@NC-NPs) is able to protect the electrode material from etching/corroding even in a tough electrolytic atmosphere. , …”
Section: Resultsmentioning
confidence: 67%
See 1 more Smart Citation
“…03-1051) of the NF substrate of Co@NC-NPs/NF. Confirmatively, the as-synthesized Co@NC-NPs catalyst retained its amorphous nature after HER . The nanochain agglomeration and maintaining the amorphous nature of the electrocatalyst reveal that the nitrogen-doped carbon matrix encapsulated on the surface of cobalt (Co@NC-NPs) is able to protect the electrode material from etching/corroding even in a tough electrolytic atmosphere. , …”
Section: Resultsmentioning
confidence: 67%
“…Based on our research group description of NiS/NF sedimentary rock as the OER catalyst, we felt that this oxidative transformation utilized oxides/hydroxides throughout the OER process of the NiS/NF electrode, which extensively enhanced the OER electrocatalytic activity . Before and after HER, durability of Co@NC-NPs demonstrated that the well-defined XRD peaks (2θ - 44, 52, and 78°) correspond to metallic Ni (JCPDS NO.…”
Section: Resultsmentioning
confidence: 99%
“…The electrocatalytic activity of ID-CoMo for the OER was also evaluated in 1 M KOH and CoO, MoO, IrO 2 and bare NF were also studied under the same conditions for comparison. The most generally accepted oxygen evolution mechanism is as follows, 43 OH + * → *OH + e − OH* + OH → *O + H 2 O + e − O* + OH → *OOH + e − OOH* + OH → O 2 + *H 2 O + e − *–active sites…”
Section: Resultsmentioning
confidence: 99%
“…Although numerous studies throughout the past few years have concentrated on transition metal-based chalcogenides, nitrides, oxides and phosphides, more emphasis has been paid to the use of materials derived from metal–organic frameworks (MOFs), which are well-known potential electrocatalysts. 7–12 Recently, NiFe-LDH has been demonstrated as the best OER catalyst in alkaline electrolytes. 13–15 However, its preparation process requires a high cost chain reaction, which makes it difficult to use in practice, hence, the need for a green synthetic method required to produce non-noble metal electrocatalysts without using additional energy, improving the number of catalytic sites by modifying their shape and structure, and enhancing the reactivity of catalytic sites by including additional components are now the essential approaches for enlightening catalytic performance.…”
Section: Introductionmentioning
confidence: 99%